Clinical signs and pathological changes in saigas infected with moniesiosis - A. R. Kozhayeva (Жәңгір хан атындағы БҚАТУ, 2024)
The necropsy findings on sick saiga antelopes reveal a complex array of pathological changes indicative of severe health deterioration. Afflicted with moniesiosis, these malnourished animals exhibit extensive abnormalities across various organ systems. Notably, subcutaneous mucus and pale mucous membranes are evident, alongside sacral congestion in the abdominal cavity. Peripheral lymph nodes are enlarged, squishy, and pale red, with reduced subcutaneous fat. Skeletal muscles display a pale pink color and soft texture, while the tongue appears softer with undefined fiber structure. Presence of blood in the larynx and tracheal cavity, along with frothy liquid in the lungs, indicates respiratory distress, compounded by emphysema affecting the upper lung lobes. Cardiac abnormalities include an enlarged heart with hemorrhage foci, stretched ventricles, and myocardium heterogeneity. Liver and gallbladder enlargement, coupled with renal abnormalities, further signify systemic compromise. The gastrointestinal tract manifests mucosal swelling, hemorrhages, and gas-filled distension, notably in the stomach and small intestine. Sebaceous lymph nodes exhibit enlargement and indistinct internal features. Conversely, the spleen displays minimal anomalies. Pancreatic edema, hemorrhage foci, and bladder hemorrhages are notable, alongside cerebral swelling and engorged blood vessels in the brain cortex. These findings collectively suggest a multi-systemic disease process, likely contributing to the animals' malnourishment and compromised health status. Further investigation into the etiology and management of this condition is imperative for wildlife conservation efforts and understanding ecosystem health dynamics.
Ғылым және білім: Ғылым, зерттеулер, білім: даму тенденциялары: акад. Қ. И. Сәтбаевтың 125 жылдығына арналған халықаралық ғылыми-практ. конф. материалдар жинағы (12 сәуір 2024 ж.) = Наука и образование: Наука, исследования, образование: тенденции развития: сб. мат. междунар. науч.-практ. конф. посвящ. 125-летию акад. К. И. Сатпаева (12 апреля 2024 г.) = Science and education: Science, research, education: development trends: unternational scientific and practical conf. dedicated to the 125th anniversary of acad. K. I. Satpayev (12 april 2024). - Орал: Жәңгір хан атындағы БҚАТУ. - 2024. - № 2 (75) : қосымша № 1. - Р. 144-151
Keywords: отечественное издание; научный журнал; конференции; saiga; ural population; necropsy; monieziasis; сайгаки; БҚАТУ; монизиоз